Transient thermal modelling of substation connectors by means of dimensionality reduction. (25th January 2017) - Abomailek, C.; Capelli, F.; Riba, J.-R.; Casals-Torrens, P.
Highlights: This paper simulates the temperature rise test for substation connectors. A one-dimensional reduction method based on the finite difference method is proposed. It uses critical information of the three-dimensional geometry of the analyzed system. Tests done in a laboratory corroborate the results of the proposed simulation method. This simulation method can be extended to other power devices. Abstract: This paper proposes a simple, fast and accurate simulation approach based on one-dimensional reduction and the application of the finite difference method (FDM) to determine the temperatures rise in substation connectors. The method discretizes the studied three-dimensional geometry in a finite number of one-dimensional elements or regions in which the energy rate balance is calculated. Although a one-dimensional reduction is applied, to ensure the accuracy of the proposed transient method, it takes into account the three-dimensional geometry of the analyzed system to determine for all analyzed elements and at each time step different parameters such as the incremental resistance of each element or the convective coefficient. The proposed approach allows fulfilling both accuracy and low computational burden criteria, providing similar accuracy than the three-dimensional finite element method but with much lower computational requirements. Experimental results conducted in a high-current laboratory validate the accuracy and effectiveness of the proposed method and its usefulness to design substation connectors and other power devices and components with an optimal thermal behavior.